Quality of care for older adults with chronic obstructive pulmonary disease and asthma based on comparisons to practice guidelines and smoking status - Chewning Betty A; Kraus Connie K; Craig Benjamin M; Davis James E (BMC, 2008)
Abstract Background The purpose of this study was to describe the prevalence of respiratory diseases in older adults and compare the demographic, health and smoking characteristics of those with and without these diseases. Furthermore, we evaluate the association between smoking status and patterns in health care and how concordant this care is with guidelines. Methods Using a nationally representative sample of 29,902 older adults who participated in the Medicare Current Beneficiary Survey (1992-2002), we compared guideline recommendations on the treatment and prevention of chronic obstructive pulmonary disease and asthma with survey utilization data, including the use of bronchodilators, spirometry and influenza vaccine. Results 26% to 30% of older adults were diagnosed with or self-reported chronic respiratory diseases; however 69% received no pharmacological treatment and 30% of patients reporting use of pharmacological treatments did not receive short-acting bronchodilator inhalers. Current smokers appeared to receive significantly less care for respiratory diseases than non-smokers or former smokers. Conclusion Disparities between recommended and actual care for older adults with chronic lung disease require further research. The needs of older adults with co-morbidities and nicotine addiction deserve special attention in care as well as guideline development and implementation.